Cathode and Anode Interlayers Based on Polymer Carbon Dots via Work Function Regulation for Efficient Polymer Solar Cells. Issue 6 (22nd January 2018) - Ji, Tianjiao; Guo, Biao; Liu, Fangyuan; Zeng, Qingsen; Yu, Chengzhuo; Du, Xiaohang; Jin, Gan; Feng, Tanglue; Zhu, Shoujun; Li, Fenghong; Yang, Bai
Abstract: In this work, the ability of tuning work function for polymer carbon dots (PCDs) is systematically studied for the first time. Their application of both cathode and anode interlayers in polymer solar cells (PSCs) is achieved. PCDs possess abundant surface functional groups, which can be modified under control. Through regulating surface groups with more electron‐donating amino (PCD‐NH2 ) or electron‐withdrawing carboxy (PCD‐COOH), PCDs can decrease or increase work function of electrode, respectively. Therefore, PCD‐NH2 can act as cathode interlayer while PCD‐COOH plays the role of anode interlayer in PSCs. The single material system to act as both interlayers is rarely reported previously. This can simplify the design of materials and the device fabrication process. In addition, PCDs are green, low‐cost, stable, and easily fabricated. Therefore, it is demonstrated that PCDs are promising for commercial interlayer materials in optoelectronic devices. Abstract : Through regulating surface groups with more electron‐donating amino or electron‐withdrawing carboxy, polymer carbon dots can decrease or increase work function of substrates, respectively. Their ability of tuning work function is systematically studied for the first time, and the application of both electrode interlayers in solar cells is achieved.